Pengaruh Kepercayaan, Harga Dan Kualitas Website Terhadap Kepuasan Pelanggan Traveloka Di Kota Medan - muhammad Arif; Sonja Nirwana Hasibuan (Fisarrearch, 2020)
The purpose of this research was to determine and analyze the influence of Trust, Price, and Website Quality on Traveloka Customer Satisfaction in the City of Medan and to know and analyze the most dominant factors to influence customer satisfaction. This research was in Medan city community who have used Traveloka service. Data analyzing method is by using descriptive analyzing method and multiple linear regression. This research is study asssociative, and this research is using primary and secondary data which was obtained by documentation study and quesionnaire whose measurment is using likert differential scale. Data was processed satistically by using SPSS (Statistic Package For the Social Sciens) software program in 2020, namely t-test, f-test, and indentification of determinant (R2 ). As the result of this research, based of simultaneous test, it is prove that the factor of trust, price and website quality have a positive and significant influence on customer satisfaction of Traveloka in the City of Medan. Particially, trust, price and website quality have a significant and positive effect on customer satisfaction. The value of Adjusted R Square 0,645% which means 64,5% of customer satisfactioncan be explained by variables trust, price, and website quality, while the remaining are 35,5% was explained by other variables which were not examined in this research